A UHF band wideband HTS filter with wide upper stopband. Issue 3 (March 2014) - Wang, Jingchen; Bin, Wei; Cao, Bisong; Guo, Xubo; Zhang, Xiaoping; Zheng, Tianning
ABSTRACT This article presents a novel six‐pole high‐temperature superconducting (HTS) UHF band filter that achieves a wide passband and a wide stopband simultaneously. This filter is designed with a new type of resonator that is composed of interdigital fingers and a vertical meander line. The center frequency of the filter is 357 MHz, and the fractional bandwidth is 28%. The measured out‐of‐band rejection is better than 55 dB up to 1438 MHz, which is four times higher than the fundamental frequency. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:600–603, 2014